Pumpkin‐Derived Porous Carbon for Supercapacitors with High Performance. Issue 12 (25th May 2016) - Bai, Suying; Tan, Guangqun; Li, Xiaoqin; Zhao, Qian; Meng, Yan; Wang, Yujue; Zhang, Yongzhi; Xiao, Dan
Abstract: Pumpkin has been employed for the first time as a renewable, low‐cost precursor for the preparation of porous carbon materials with excellent performance. Unlike most other precursors, pumpkin is rich in sugars and starch, and it has advantageous properties for large‐scale production. The as‐prepared materials adopted a unique morphology that consisted of numerous fused sphere‐like carbon grains with a high specific surface area (2968 m 2 g −1 ), abundant micro and mesopores, and excellent electrochemical properties. The pumpkin‐derived activated carbon (PAC) material not only exhibited a high specific capacitance of 419 F g −1, but also showed considerable cycling stability, with 93.6 % retention after 10 000 cycles. Moreover, a symmetrical supercapacitor that was based on PAC showed a high energy density of 22.1 W h kg −1 in aqueous electrolyte. These superior properties demonstrate that PAC holds great promise for applications in electrochemical energy‐storage devices. Abstract : Smashing pumpkins : Pumpkin has been employed as a renewable, low‐cost precursor for the preparation of porous carbon materials that exhibited outstanding performance: high specific capacitance (419 F g −1 ); good long‐term cycling stability, with 93.6 % retention after 10 000 cycles; and an energy density of 22.1 W h kg −1 in aqueous electrolyte.